2019
DOI: 10.1021/acsami.9b19745
|View full text |Cite
|
Sign up to set email alerts
|

Constructing an Antibiofouling and Mineralizing Bioactive Tooth Surface to Protect against Decay and Promote Self-Healing

Abstract: Numerous methods have been investigated to manage dental caries, one of the top three diseases threatening human health as reported by the World Health Organization. An innovative strategy was proposed to prevent dental caries and achieve self-healing of the decayed tooth, and a novel bioactive peptide was designed and synthesized to construct an antibiofouling and mineralizing dual-bioactive tooth surface. Compared to its original endogenous peptide, the synthesized bioactive peptide showed statistically sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 40 publications
3
54
0
Order By: Relevance
“…75,76 Molecular dynamics simulations showed that the binding mechanism between histatin 5 and HA was the negatively charged amino acid residue Asp 2 and the positively charged amino acid residues Lys 6 , Arg 13 , Lys 14 and Lys 18 . 37 Because of the antifungal activity and the affinity ability to HA of histatin-5, Candida albicans strain colonization was significantly inhibited on the histatin-5-coated HA surface, even after 1440 min. 39…”
mentioning
confidence: 99%
“…75,76 Molecular dynamics simulations showed that the binding mechanism between histatin 5 and HA was the negatively charged amino acid residue Asp 2 and the positively charged amino acid residues Lys 6 , Arg 13 , Lys 14 and Lys 18 . 37 Because of the antifungal activity and the affinity ability to HA of histatin-5, Candida albicans strain colonization was significantly inhibited on the histatin-5-coated HA surface, even after 1440 min. 39…”
mentioning
confidence: 99%
“…The replacement of Gln and Asn with Glu and Asp in the tail sequence of TD7 resulted in an increased positive charge of TVH-19. This positive charge of the peptide contributes to a higher binding affinity to the tooth surface through the electrostatic attraction forces of positively charged amino acid residues with negatively charged PO 4 3− of HA [35]. After remineralization, the microscopic observation of dentin morphology showed obvious remineralization and dentinal tubule occlusion on the surface of the dentin in group A (50 µg/mL TVH-19) and group B (100 µg/mL TVH-19) after treatment for 4 weeks, with a dosage effect.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study investigated the applicability of a modified dual function (antimicrobial and remineralising activities) AMP, phospherine-grafted-histatin 5, for higher HApbinding affinity to tooth surfaces in the treatment of decayed teeth [180]. The AMP histatin 5 contains cationic amino acid residues which elicit a bactericidal effect via inducing membrane permeability and damage to intracellular DNA of microbes as well as promote its adsorption to tooth surfaces for forming a bioactive coating with antibiofouling effects and in situ self-healing of carious lesions [180]. In another study, Zhang et al grafted the antimicrobial polyphemusin I (PI) to diphosphoserine (DPS) for the synthesis of a tooth-binding DPS-PI AMP.…”
Section: Amp Tooth-binding Strategiesmentioning
confidence: 99%